1995
DOI: 10.1111/j.1365-2710.1995.tb00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Influencing the prescribing behaviour of physicians: a metaevaluation

Abstract: Many different interventions have been used to influence the prescribing behaviour of physicians, and qualitative evaluations (metaethnography) of such interventions have been reported. So far quantitative evaluations of such interventions have not been reported; this study is an attempt in that direction. Twenty-six published studies (January 1979-September 1991) on the interventions for influencing the prescribing behaviour of physicians were pooled and effect sizes were extracted. Mean effect size (Zr) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…13 When we separated CME outcomes into the 3 different outcomes, we found a moderate effect size between CME and physician knowledge and a small effect size between CME and physician performance. We also obtained a small effect size between CME and patient outcomes over 8 studies that reported these outcomes.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…13 When we separated CME outcomes into the 3 different outcomes, we found a moderate effect size between CME and physician knowledge and a small effect size between CME and physician performance. We also obtained a small effect size between CME and patient outcomes over 8 studies that reported these outcomes.…”
Section: Discussionmentioning
confidence: 83%
“…They found that widely used CME delivery methods such as conferences had little direct effect on improving professional practice. Pippalla and colleagues' meta-analysis 13 of 43 studies showed that the combination of active and passive strategies resulted in a better effect on physicians' prescribing behavior than other interventions. Davis and associates' 7-study meta-analysis 7 failed to show a significant effect of didactic educational methods on the outcomes of CME (d = 0.34); however, they did find that interactive and mixed educational sessions were associated with a significant effect on physicians' performance (d = 0.67).…”
mentioning
confidence: 99%
“…Furthermore, Davis and his colleagues found that a mixed methods approach to CME delivery, such as practice-based interventions and outreach visits, was more effective than didactic CME sessions but seldom used. Related studies found CME activities that focused on specific objectives, targeted one specialty group, and utilized active pedagogy as the main method of knowledge delivery had a greater impact on changing physician practices to improve patient care and did a better job of identifying and mitigating physician gaps in knowledge (Davis, O'Brien, Freemantle, Wolfe, Mazmanian & Taylor-Vaisey, 1999;Grol, 2002;Monsouri & Lockyer, 2007;Pippalla, Riley & Chinburapa, 1995). Although a mixed methods approach to CME delivery has had positive outcomes, flaws in the CME process still exist.…”
Section: Continuing Medical Educationmentioning
confidence: 99%
“…60,61 There are many promising approaches that have been shown to be effective in changing behavior. For instance, educational outreach programs in which a trained person meets with providers in their practice setting to provide information with the intent of changing the provider's performance, [62][63][64][65][66][67][68][69] distribution of published recommendations for clinical care (including practice guidelines, audiovisual materials, pocket cards, electronic mail, posters, manuals), 70 and seminars and interactive workshops 71 are all shown to be effective. Other interventions include a summary of clinical performance over a specified period of time, highlighting areas of strength and weakness (audit and feedback), 69 advanced organizers, listserv (an electronic correspondence tool), and reminders.…”
Section: Discussionmentioning
confidence: 99%